Relativistic Many-body Calculations for Electric Dipole Moments in \(^{129}\)Xe, \(^{199}\)Hg, \(^{223}\)Rn, \(^{225}\)Ra and \(^{171}\)Yb Atoms (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
We present and compare the results of permanent electric dipole moments (EDMs) of various closed-shell atoms due to the nuclear Schiff moment (NSM) and the tensor-pseudotensor (T-PT) interactions between the atomic nuclei and electrons. In order to highlight the role of electron-correlation effects in obtaining accurate EDM results, we employ a number of relativistic many-body methods including coupled-cluster theory at different degrees of approximation. On combining our results obtained from the relativistic coupled-cluster (RCC) at the levels of singles and doubles excitations (CCSD method) with the available EDM measurements we obtain accurate bounds on the couplings \(S\) and \(C_T\) associated with the respective NSM and T-PT interactions. The most precise EDM measurement on \(^{199}\)Hg in combination with our CC results yield limits on the above couplings as \(S
Keywords: Coupled-cluster theory; Nuclear Schiff moment; Tensor-pseudotensor interaction; CPviolation; Electron correlation